Penerapan Akuntansi Keluarga Dalam Pengelolaan Keuangan Rumah Tangga Pasangan Milenial - Lureng, Nikolaus; Dekrita, Yosefina Andia; Dilliana, Siktania Maria (Universitas Nusa Nipa Maumere, 2025)
This research aimed to analyze the implementation of family accounting in household financial management among millennial couples. The focus of the research included family financial management, which was measured through the indicators of budgeting, recording, decision-making, and long-term financial planning, as well as financial management behavior. The method used was qualitative with a case study approach, through in-depth interviews with millennial couples as informants. The research findings showed that millennial couples had begun to apply family accounting, although it was still simple and mostly not formally documented. This practice is in line with positive accounting theory, which explains rational behavior in financial decision-making. In addition, the Japanese principle of Kakeibo was relevant as a practical approach because it emphasizes recording, awareness, and evaluation of expenditures. Therefore, it will be important in realizing household financial management that is more directed, healthy, and sustainable.